Collaborative online learning: implementation of vocational alignment in accordance with industry's needs - Abdurrahman, Isnaini Sholihan; Mahmudah, Fitri Nur; Paryono, P; Saryadi, Saryadi; Cahyono, Sulistio Mukti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
The current acceleration of digital transformation requires the adaptability of schools, teachers, students, and school partner institutions, namely the industry. The purpose of this study is to reveal the important components and indicators in the online collaborative learning process as part of a vocational alignment program. This study uses a qualitative case study approach. The research model uses the Miles Huberman interactive model. The participants of this research are productive teachers, alumni, and instructors from industry. This research was conducted in Yogyakarta. Data analysis was carried out with the help of Atlas.ti software version 9. The validity of the data was using source triangulation. The results of this study are that there are main components that must exist in collaborative on-line learning, namely pedagogical learning environments, instructions, digital tools, apply methods, and development of critical thinking. Recommendations for this study are given to all teachers who teach in vocational high schools and all instructors as partner schools to improve the quality of learning as technology develops. So that they can take advantage of technology in learning through online learning collaborations.